Friend or Foe: Regulation, Downstream Effectors of RRAD in Cancer - Zhangyue Sun; Yongkang Li; Xiaolu Tan; Wanyi Liu; Xinglin He; Deyuan Pan; Enmin Li; Liyan Xu; Lin Long (Biomolecules, 2023)
Ras-related associated with diabetes (RRAD), a member of the Ras-related GTPase superfamily, is primarily a cytosolic protein that actives in the plasma membrane. RRAD is highly expressed in type 2 diabetes patients and as a biomarker of congestive heart failure. Mounting evidence showed that RRAD is important for the progression and metastasis of tumor cells, which play opposite roles as an oncogene or tumor suppressor gene depending on cancer and cell type. These findings are of great significance, especially given that relevant molecular mechanisms are being discovered. Being regulated in various pathways, RRAD plays wide spectrum cellular activity including tumor cell division, motility, apoptosis, and energy metabolism by modulating tumor-related gene expression and interacting with multiple downstream effectors. Additionally, RRAD in senescence may contribute to its role in cancer. Despite the twofold characters of RRAD, targeted therapies are becoming a potential therapeutic strategy to combat cancers. This review will discuss the dual identity of RRAD in specific cancer type, provides an overview of the regulation and downstream effectors of RRAD to offer valuable insights for readers, explore the intracellular role of RRAD in cancer, and give a reference for future mechanistic studies.